A COMMENT ON SIEGFRIED'S FIRST LESSON IN ECONOMETRICS. (17th October 2013) - ELDRIDGE, DAMIEN S.
<x xml:space="preserve">Abstract</x> In an insightful, and delightfully short, paper that was published in the Journal of Political Economy in 1970, Siegfried provided an important lesson about econometric methodology for all budding young econometricians. Unfortunately, there is a mistake in that paper. This short comment provides a simple correction for that mistake. This correction will hopefully enable econometrics students to obtain the fundamental insights from Siegfried's paper with less confusion than might otherwise have been the case. (JEL A20, C01, C10)